Digital Marketing Communication Strategy Through Instagram in Enhancing Brand Awareness: An AISAS Perspective Study of Nasi Bebek Bahagia (2025) - Afdhol Fikri Astika; Adhianty Nurjanah; Denis Hida Lutfiana Stefani (Jogjakarta Communication Conference (JCC), 2026)
Instagram, as a visual based social media platform, has become a primary medium for young consumers in seeking references before making purchasing decisions. In Yogyakarta’s culinary industry, Instagram plays a strategic role in enhancing brand awareness and building relationships with consumers through interactive features such as Feed, Stories, and Reels. Increasing market competition encourages businesses to implement adaptive digital marketing communication strategies aligned with consumer behavior. This study aims to describe the digital marketing communication strategy of @nasibebek.bahagia on Instagram in enhancing brand awareness using the AISAS approach (Attention, Interest, Search, Action, Share). The research employs a descriptive qualitative approach within a post-positivist paradigm. Data were collected during the 2025 operational period through in-depth interviews with the business owner, customers, and content marketing, as well as documentation of Instagram content. The findings indicate that the Attention and Interest stages are developed through consistent visual aesthetics and content relevant to the student segment. The Search stage is facilitated by providing clear information through the feed and highlights features, which subsequently encourages the Action stage in the form of store visits and purchasing decisions. The Share stage emerges through consumer participation in sharing their experiences on social media. The findings demonstrate that this strategy plays a significant role in strengthening brand recognition and enhancing brand recall among the target consumers. Overall, although the strategy has not been formally structured through a fixed content calendar, the consistent utilization of Instagram features has proven effective in building and strengthening Nasi Bebek Bahagia’s brand awareness.